Efektivitas Bantuan Rombong BAZNAS Kota Surabaya dalam Pemberdayaan Usaha Mikro Mustahik - Khusnul Khotimah, Aisyah; Falasifah, Nihlatul (PROGRESIF: Jurnal Dakwah, Sosial, dan Komunikasi, 2024)
The issue of poverty, particularly in developed cities like Surabaya, requires appropriate and sustainable solutions. The National Zakat Agency (BAZNAS) of Surabaya City has introduced five main programs: Surabaya Berdaya, Surabaya Cerdas, Surabaya Peduli, Surabaya Sehat, and Surabaya Takwa. One of BAZNAS' efforts to improve the economic conditions of mustahik is through the Rombong Berkah program, which aims to empower the community by providing carts to mustahik as initial capital to start and grow their small businesses. This study aims to evaluate the effectiveness of the Rombong Berkah program in enhancing the economic well-being of mustahik and to analyze its potential in fostering the transformation of mustahik into muzzaki. This evaluation is expected to provide deeper insights into the program's contribution to community economic empowerment, as well as identifying the challenges and opportunities in its implementation